INVESTIGATION OF GROUNDWATER POLLUTION BY PETROLEUM HYDROCARBON FROM GAS STATIONS IN YOGYAKARTA, INDONESIA - Suphia Rahmawati; Any Juliani; Wahyuningtyas Perwita Sari; Azkiyatul Bariroh (Teknik Lingkungan Universitas Islam Indonesia, 2018)
Gas stations are a common source of groundwater contamination by petroleum hydrocarbons. These pollutants are a health concern when people come in contact with the contaminated water when pumping from polluted wells, for example. However, in Indonesia this problem remains largely ignored, despite some prominent leakage incidents at gas stations. The purpose of this study is to investigate the groundwater contamination by petroleum hydrocarbon from gas station in the greater Yogyakarta area in Indonesia. Screening criteria such as construction standards, reported leakage incidents, and geological and hydrogeological condition were used to identify gas stations with high risk of water contamination by petroleum hydrocarbon. Gas station with close proximity with dug wells in which its water had been used for human daily consumption was selected for further analysis. Groundwater samples were then collected from dug wells located in the vicinity to this selected gas station and then analyzed for benzene, toluene, ethylbenzene, xylene (BTEX) by gas chromatography/mass spectrometry. Of the six sampling points, BTEX were detected with concentrations ranging from 0,008 to 25,631 ppb. Concentration of benzene at sampling point 3 exceed the standards of Indonesian drinking water quality and WHO. These findings indicate that BTEX groundwater pollution may be a health hazard of currently unknown proportion in the greater Yogyakarta area. It is recommended to assess health risk associated with human daily consumption of BTEX polluted groundwater and also to test groundwater at all gas stations in this area and remediate those affected by BTEX.